Is religious education possible: a philosophical investigation (Review of the book by Michael Hand, London & New York, Continuum, 158 pp.(2006) ISBN: 0826491502) - Hussien, Suhailah (Euro-Mediterranean Centre for Educational Research, University of Malta., 2010)
Many schools assume that it is logically possible to teach religious education in schools and that it can be taught in a non-confessional manner. However, some philosophers have argued that non-confessional religious education is not possible without imparting religious beliefs. This book is considered significant because it attempts to explore logically the debate by presenting arguments and views of different philosophers. Hand begins his book by outlining the main arguments in the introduction chapter, particularly focusing on the possibility of imparting religious understanding without imparting religious belief. His concern is to discuss whether teaching religious education in schools is a futile practice, examining the claim that ‘non-confessional religious education is a logically incoherent enterprise because religious understanding presupposes religious belief articles’ (p. 2)....